PENANGANAN DISPEPSIA PADA LANJUT USIA - Wibawa, I Dewa Nyoman (journal of internal medicine; Vol. 7, No. 3 September 2006)
In elderly patients with dyspeptic syndrome, organic causes more prevalence rather than fungsional related disorders. The use of Nonsteroid Anti Inflammatory Drugs (NSAIDs) and H. pylori infection play as important role as causes of organic dyspepsia in eldery patients. There are some changes in upper gastrointestinal tract which is related to aging process, especially in mucosal defance mechanism. The changes in aggressive factors are only a few. Diagnostic approach with endoscopic examination is necessary in eldery patients with dyspeptic syndrome to role out the possibility of organic origin. The management of dyspepsia in eldery patients needs comprehensive approach because clinical presentation usually asymptomatic, the use of polypharmacy, co-morbidity, and the probability of organic origin as a cause needs to be proved since the beginning.
Keywords: dyspepsia, elderly